PERFORMANCE ANALYSIS OF INPATIENT UNIT “ANGGREK PAVILION” AT RSAL DR. MINTOHARDJO IN 2014 - 2017 USING MANAGEMENT APPROACH - Fidela Eniraisa; Budi Hidayat (Proceedings of the International Conference on Applied Science and Health, 2018)
Background:. The increasing number of hospitals built by both private and government parties to make patients can choose the hospital they want, so that will lead to increased competition between hospitals. It requires a hospital to be ready to compete and be more creative in developing its services. One of the most important elements in a hospital is the management department who play an active role. This study aims to explain the relationship between the five M’s of management with the performance improvement of an inpatient unit ”Orchid Pavilion”. So the other hospital with a low performance may be more concerned with the five management factors at the hospital and this study can be a good example which can be applied by other hospitals. Methods: This research was conducted at inpatient unit “Orchid Pavilion”Rumah Sakit Angkatan Laut (Navy Hospital) Dr. Mintohardjo. The research was conducted by qualitative method, that is to conduct in-depth interview with Head of Orchid Pavilion and Deputy Head of Orchid Pavilion, and study data obtained from Medical Administration Department Rumah Sakit Angkatan Laut (Navy Hospital) Dr. Mintohardjo. Results: The results show that there has been an improvement of performance in inpatient unit “Orchid Pavilion” and many improvement on the five M’s in management (Men, Money, Materials, Machines, and Method) resulting in significant increase of Bed Occupancy Ratio value in the room. Conclusions: Improvements in five M’s in management greatly affect the improvement of performance in inpatient unit “Orchid Pavilion” Rumah Sakit Angkatan Laut (Navy Hospital) Dr. Mintohardjo. The five M’s in management (Men, Money, Materials, Machines, and Method) have a strong role in improving the performance of inpatient unit “Orchid Pavilion”.